Effectiveness of mind mapping for learning in a real educational setting. Issue 1 (11th November 2020) - Gavens, Nathalie; Doignon-Camus, Nadège; Chaillou, Anne-Clémence; Zeitler, Alexandre; Popa-Roch, Maria
Abstract: The purpose of the experiment reported here was to investigate whether mind mapping adds any value as a studying technique to that of testing. We compared the effects of mind mapping on acquisition on graders (N = 68) in a secondary school in two separate consecutive periods of learning called series. In series 1, half the students used mind mapping plus testing to learn the content of the course, and other half used testing alone. In series 2, the organization was reversed, in a repeated measure design. The results revealed that students' performances improved during the two series, but that they did not progress more when they used mind mapping. These results indicate that the popularity of mind mapping in learning practices does not reflect its effectiveness. We discuss our results in relation with the need for teaching practices to be based on theories of evidence-based education rather than on intuition only.